THE EFFECT OF HAND PUPPET MEDIA ON THE SPEAKING SKILLS OF SECOND GRADE STUDENTS AT MI AS-SYAFI’IYAH 10 GUNUNG SINDUR - Lu'luil Maknun; Nia Fitriyana (PT. Jurnal Center Indonesia Publisher, 2025)
The purpose of this study is to determine the significance level of the effect of using hand puppet media on the speaking skills of second-grade students at MI As-Syafi’iyah 10 Gunung Sindur. This research employed a quasi-experimental method with a quantitative approach. The sampling technique used was non-random purposive sampling, with two classes selected as samples, each consisting of 32 students. The data collection technique used in this study was an oral test instrument, designed using a non-equivalent control group design. The results showed that the average score of the experimental class was 45.31 in the pre-test and 67.81 in the post-test. Meanwhile, the control class scored an average of 44.84 in the pre-test and 46.56 in the post-test. The data were tested for normality and found to be normally distributed. The homogeneity test results showed a significance value of 0.308 > 0.05, indicating that the data are homogeneous or have the same variance. The findings revealed that the use of hand puppet media had a significant effect on students' speaking skills. The hypothesis testing using a Paired Sample T-Test showed a significance level of 0.000 < 0.05, indicating that the result is statistically significant. Therefore, the null hypothesis (H₀) is rejected, and the alternative hypothesis (H₁) is accepted, meaning there is a significant difference in students’ speaking skills before and after being taught using hand puppet media.